Supporting the Developmet of Language Learning Strategies through Feedback - Petrová, Eliška (Univerzita Pardubice, 2015)
This bachelor thesis deals with the usage of feedback in the field of English language teaching. The main focus is placed on such feedback forms, which enable the integration of language learning strategies, and thus can support the development of autonomy. The theoretical part of the thesis deals with the interconnection of autonomy, assessment, feedback, and language learning strategies. The teacher, who is in the focus of attention here, is described as a necessary person providing feedback to learners. This paper tries to clarify the ways feedback can contribute to autonomy development, particularly language learning strategies that significantly facilitate the learning process. The practical part of this thesis examines which feedback forms are used in practice and if they contribute to language learning strategies development.
Keywords: teachers; autonomy; assessment; feedback; error correction; language learning strategies; učitelé; autonomie; hodnocení; zpětná vazba; oprava chyb; jazykové učební strategie